Assessing Students’ Strategic Competence in Speaking English - TERESHCHUK, Diana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article proposes criteria for testing university students’ strategic competency in speaking. The roots of the derivation of the four criteria and their indicators is the demands for the future specialists – university students, the essence and distinctive peculiarities of strategic competence, the specificity of speaking as a skill and as an activity, the modern tendencies in evaluation processes. Hence, such criteria with the corresponding indicators for evaluation were established: cognitive, communicative, goal-seeking, educational-compensatory. Studying specific tasks for assessment and developing tools of evaluating strategic competence in writing and interaction activities open new prospects for further educational research.